Third Eye for Visually Impaired People - G. Nikhil Sai, Dr. P. Kalyanasundaram (International Journal of Advanced Science and Technology, 2020)
Visual deficiency, the most serious type of visual debilitation, can decrease individuals’ capacity to perform day by day undertakings, and move about unaided. Visual data is the reason for most navigational errands, so outwardly hindered individuals are at inconvenience since vital data about the encompassing condition isn’t accessible. With the ongoing advances in comprehensive innovation it is conceivable to stretch out the help given to individuals with visual impedance amid their portability. The point of this paper is to approach about a course help change for ostensibly hindered and apparently debilitated with worked in furnishes the customer with information to go about fit as a fiddle, regardless of whether indoor or outside, with a simple GUI to utilize. Obviously, an obstruction region structure as to diminish course challenges of the apparently blocked. The proposed gadget distinguishes the nearest obstruction by method of ultrasonic sensors, and gives an admonition with respect to its abuse to light up the apparently lacking.